Dl-3-n-Butylphthalide Rescues Dopaminergic Neurons in Parkinson’s Disease Models by Inhibiting the NLRP3 Inflammasome and Ameliorating Mitochondrial Impairment - Que, Rongfang; Zheng, Jialing; Chang, Zihan; Zhang, Wenjie; Li, Hualing; Xie, Zhenchao; Huang, Zifeng; Wang, Hai-Tao; Xu, Jiangping; Jin, Dana; Yang, Wanlin; Tan, Eng-King; et al. (Frontiers in Immunology, 2021)
Background Neuroinflammation and mitochondrial impairment play important roles in the neuropathogenesis of Parkinson’s disease (PD). The activation of NLRP3 inflammasome and the accumulation of α-synuclein (α-Syn) are strictly correlated to neuroinflammation. Therefore, the regulation of NLRP3 inflammasome activation and α-Syn aggregation might have therapeutic potential. It has been indicated that Dl-3-n-butylphthalide (NBP) produces neuroprotection against some neurological diseases such as ischemic stroke. We here intended to explore whether NBP suppressed NLRP3 inflammasome activation and reduced α-Syn aggregation, thus protecting dopaminergic neurons against neuroinflammation. Methods In our study, we established a MPTP-induced mouse model and 6-OHDA-induced SH-SY5Y cell model to examine the neuroprotective actions of NBP. We then performed behavioral tests to examine motor dysfunction in MPTP-exposed mice after NBP treatment. Western blotting, immunofluorescence staining, flow cytometry and RT-qPCR were conducted to investigate the expression of NLRP3 inflammasomes, neuroinflammatory cytokines, PARP1, p-α-Syn, and markers of microgliosis and astrogliosis. Results The results showed that NBP exerts a neuroprotective effect on experimental PD models. In vivo, NBP ameliorated behavioral impairments and reduced dopaminergic neuron loss in MPTP-induced mice. In vitro, treatment of SH-SY5Y cells with 6-OHDA (100uM,24 h) significantly decreased cell viability, increased intracellular ROS production, and induced apoptosis, while pretreatment with 5uM NBP could alleviated 6-OHDA-induced cytotoxicity, ROS production and cell apoptosis to some extent. Importantly, both in vivo and in vitro, NBP suppressed the activation of the NLRP3 inflammasome and the aggregation of α-Syn, thus inhibited neuroinflammation ameliorated mitochondrial impairments. Conclusions In summary, NBP rescued dopaminergic neurons by reducing NLRP3 inflammasome activation and ameliorating mitochondrial impairments and increases in p-α-Syn levels. This current study may provide novel neuroprotective mechanisms of NBP as a potential therapeutic agent.